2022
DOI: 10.3389/fpubh.2022.912816
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Lifestyle Changes in Saudi Adults With Types 1 and 2 Diabetes

Abstract: ObjectiveWe aimed to evaluate and compare the impact of COVID-19 lockdown on lifestyle changes and other common related effects of the lockdown in Saudi adults with diabetes mellitus (DM), both type 1 (T1D) and type 2 diabetes (T2D).Methods265 T1D and 285 T2D individuals were included in this cross-sectional survey during lockdown using an online questionnaire and compared with 297 participants without DM. Variables included demographics, treatment changes, use of supplements, change in sleeping habits and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Previous studies suggested that the COVID-19 pandemic had a significant impact on diabetes self-management in the KSA population. The challenges faced by individuals with diabetes include reduced compliance with medical treatment, lifestyle changes, increased psychological distress, and limited access to healthcare services; however, the findings of this study have several important implications related to diabetes care in the post-COVID-19 era [ 10 , 11 , 12 , 13 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that the COVID-19 pandemic had a significant impact on diabetes self-management in the KSA population. The challenges faced by individuals with diabetes include reduced compliance with medical treatment, lifestyle changes, increased psychological distress, and limited access to healthcare services; however, the findings of this study have several important implications related to diabetes care in the post-COVID-19 era [ 10 , 11 , 12 , 13 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, three additional items on overall COVID-19 impact upon diabetes control, diet, and exercise were asked, to end up with a total of 19 questions. The scale includes five subscales: glucose management (1,4,6,10,12), diet control (2,5,9,13), physical activity (8,11,15), use of health services (3,7,14), and overall COVID-19 impact (17,18,19). Item 16 was not included in any subscales.…”
Section: Data Collection and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Another study from the Middle Eastern region revealed that COVID-19 lockdown-associated lifestyle changes, such as decreased physical activity, were more prevalent in individuals with T1DM as compared to control group, potentially explaining undesirable weight gain. 20 …”
Section: Discussionmentioning
confidence: 99%
“…This retrospective longitudinal study continued an educational interventional program conducted by the Chair for Biomarkers in Chronic Diseases (CBCD), King Saud University, in collaboration with the Saudi Charitable Association of Diabetes [ 27 , 28 , 29 , 30 , 31 ]. The study utilized a cluster-randomized sampling approach for selecting 60 high and secondary schools in Riyadh city to conduct an educational program among students and teachers on the rising prevalence of metabolic disorders in Saudi Arabia, including obesity, diabetes, and metabolic syndrome (MetS).…”
Section: Methodsmentioning
confidence: 99%